Kekuatan Konten dan Engagement: Mampu Membangun Kepercayaan Merek Hingga Keputusan Pembelian - Arum Wahyuni Purbohastuti; Wenda Wahyu Christiyanto; Farah Putri Wenang Lusianingrum; Galih Ginanjar Saputra (Universitas Sultan Ageng Tirtayasa, 2025)
The purpose of this study is to examine how user-generated content (UGC) and social media engagement (SME) impact purchasing decisions (PD), with Brand Trust (BT) as a mediating variable. The study focuses on social media users who actively engage with brand content. 130 respondents were obtained through an online questionnaire. Data analysis was conducted using WarpPLS 5.0 and the PLS-SEM (Partial Least Squares–Structural Equation Modeling) method. The results show that UGC and SME have a significant influence on BT and PD, and BT also has a significant influence on PD. In addition, this study found that BT partially mediates the relationship between UGC and SME on PD. The study concludes that brand trust is an important factor that bridges consumer engagement in social media and user-generated content in influencing their decision to purchase something.